Multiple Charge Transfer Dynamics in Colloidal CsPbBr3 Perovskite Quantum Dots Sensitized Molecular Adsorbate - Maity, Partha; Dana, Jayanta; Ghosh, Hirendra N (Journal of physical chemistry. C, 2016)
Ultrafast charge-transfer (CT) dynamics has been verified in CsPbBr3 (CPB) quantum dot (QD)–4,5-dibromofluorescein (DBF) composite materials, which form a strong CT complex in the ground state and can absorb more photons in the red region of the solar spectrum. Cyclic voltammetry and steady state luminescence studies suggest that the conduction (CB) and valence bands (VB) of CPB lie, respectively, below the LUMO and the HOMO of the DBF molecule. Steady state and time-resolved luminescence measurements with selective photoexcitation reveal the photoexcited hole transfer from CPB QDs to the DBF molecule, which is thermodynamically viable. Additionally, a red-shifted PL band was detected upon excitation of the CT complex that has been attributed to CT luminescence. Femtosecond transient absorption measurements have been performed to measure the hole transfer and direct electron transfer processes in the composite system and have been measured to be 1–1.25 ps and <100 fs, respectively. Dual behavior of the DBF molecule in the composite material, like hole transporting and sensitizing of the CPB perovskite, can drastically improve the solar conversion efficiency.